A linguagem da avaliação nas semioses verbal e visual: marcas avaliativas em reportagens verbo-visuais - Guilherme Rocha Brent (2024)
This research deals with the intersection of the appraisal system with photojournalism by analysing verbal and visual evaluative marks in reportage genre, which consists of linguistic and visual elements arranged in the textual space in order to construct a certain representation of the experience. Events reported by the press are part of a complex and artificial selection operation – which implies which actions to describe, which social actors to put in the foreground, which voices to insert in the news and other choices. This is guided by social, political and economic interests, which are reflected in the semiotic resources adopted in the construction of the news text. Therefore, when we investigate verbal and visual evaluative marks in verbal-visual news, we are analysing how each semiotic choice reflects an evaluative positioning. The corpus – which covers que political scenario surrounding Jair Bolsonaro during the pandemic period in Brazil – is collected on the website of the magazine IstoÉ. The study presented in this thesis has a systemic-functional – more specifically evaluative (MARTIN; WHITE, 2005) – and photojournalistic bases (SOUSA, 1997; 2000; 2004; CAPLE, 2013). Verbal and visual evaluative marks were analyzed in the domain of attitude, through the categories of affect, judgment and appreciation; photographs, through categories of plane, angle and caption. To support the descriptions and analyzes of the identified evaluations, the concepts of discourse, ideology (FAIRCLOUGH, 1995b; 2003), editorial line (TRAQUINA, 1993) and public image (WEBER, 2004; 2009) were used. After analyzing the corpus, it was noted that the choices of attitudinal meanings on the verbal and visual planes converge towards a critical and moralizing discourse to the detriment of Jair Bolsonaro. This convergence is, therefore, the result of an intentional process of lexical, grammatical and semantic choices that occur verbally and visually. It was possible to identify, this way, how the narratives are supported by a discourse that criticizes, condemns and represses the political stances taken by Bolsonaro during the pandemic period in Brazil – a discourse called infamous (THOMPSON, 2002). Furthermore, the survey of the types of attitudes carried out verbally revealed the predominance of negative evaluations, notably those in the judgment subsystem. This allowed us to identify the construction and negotiation of a depreciatory political image for Bolsonaro, ratified in the photographs selected to narrate each of the facts described.